Investigations on the effect of light reduction on yield, growth, and secondary metabolites of lemon balm (Melissa officinalis L.) - Russo, Marco; Justus Liebig University Giessen (My University, 2019)
Lemon balm (Melissa officinalis L.) is an important medicinal and aromatic plant belonging to the Lamiaceae family. Besides essential oil, lemon balm also contains several phenolic substances, with rosmarinic acid (RA) being the most important one. For a pharmaceutical use, a minimal RA content of 1% is required by the European Pharmacopoeia. The use of various kinds of plant protection nets is increasingly popular. They have been proposed for the prevention of leafhopper infestations in the cultivation of medicinal and aromatic plants, like lemon balm, as well. As they also lead to a light reduction, this work wanted to determine how growth, yield, and quality of lemon balm plants are influenced by the use of nets with shading properties at two different locations. A moderate light reduction of about 10-15% was tested at the experimental site in Gross-Gerau (GG), and a stronger light reduction of about 50% in Rauischholzhausen (RH). The plant stands were harvested for three years, in two cuts per year. For the determination of possible interaction effects, different genotypes and harvest stages were investigated as additional factors. Regarding the plant parameters, no significant influence of the moderate light reduction was observed. The stronger light reduction, however, led in many cases to changes that are typical signs of the shade avoidance syndrome of the plants. The yield level in RH was on average higher than in GG. No effect of the moderate shading in GG on biomass or leaf yield, dry matter content of the leaves, or leaf:stem-ration was observed. The stronger light reduction in RH, however, decreased the dry matter content of the leaves, and, partly, biomass and leaf yield, especially for quite recently shaded plants. The measured quality parameters total phenolic content (TPC), antioxidant capacity (ORAC assay), as well as essential oil and RA content were not reproducibly affected by the moderate light reduction in GG. Also under the stronger light reduction in RH, essential oil content was not reproducibly influenced. TPC, antioxidant capacity, as well as RA content, however, were decreased under the stronger light reduction in RH. No reproducible pattern could be observed regarding a genotype effect on the tested growth, yield, and quality parameters, except for the essential oil content, which was highest in the genotype Lemona . Differences were greater between the two experimental sites, indicating a greater importance of the environmental conditions than the genotypes for the investigated parameters. It can be concluded that the use of plant protection nets with a stronger light reduction can be regarded as negative under the tested cultivation conditions. However, the use of plant protection nets with only a moderate light reduction seems to be possible for the cultivation of lemon balm under comparable cultivation conditions.

Die Zitronenmelisse (Melissa officinalis L.) ist eine wichtige Arznei- und Gewürzpflanze aus der Familie der Lamiaceae. Neben ätherischem Öl sind in der Zitronenmelisse phenolische Verbindungen, darunter vor allem Rosmarinsäure (RA), enthalten. Für eine arzneiliche Nutzung ist im Europäischen Arzneibuch ein Mindestgehalt an RA von 1 % vorgeschrieben. Der Einsatz verschiedenartiger Pflanzenschutznetze gewinnt zunehmend an Bedeutung. Für den Anbau von Arznei- und Gewürzpflanzen, wie beispielsweise Zitronenmelisse, werden sie zum Schutz vor Zikadenbefall empfohlen. Da ihr Einsatz auch zu einer Lichtreduktion führt, sollte diese Arbeit den Einfluss von schattierenden Netzen auf Wachstum, Ertrag und Qualität der Zitronenmelisse unter Feldbedingungen an zwei unterschiedlichen Standorten untersuchen. Eine moderate Lichtreduktion von ca. 10-15 % wurde am Versuchsstandort Groß-Gerau (GG) und eine stärkere Lichtreduktion von ca. 50 % in Rauischholzhausen (RH) realisiert. Der Pflanzenbestand wurde über drei Jahre mit jeweils zwei Aufwüchsen pro Jahr beerntet. Um mögliche Interaktionseffekte zu erkennen, wurden zusätzlich zur Beschattung verschiedene Genotypen und Erntezeitpunkte als Prüffaktoren untersucht. Die untersuchten Pflanzenparameter wurden durch die moderate Lichtreduktion nicht signifikant beeinflusst. Die stärkere Lichtreduktion hingegen führte in vielen Fällen zu Veränderungen, die als typische Schattenvermeidungsreaktion der Pflanzen zu werten sind. Das Ertragsniveau der Zitronenmelisse war in RH höher als in GG. Die moderate Beschattung in GG hatte keinen signifikanten Einfluss auf Biomasse- bzw. Blattertrag, Blatt-Trockenmassegehalt sowie das Blatt-Stängel-Verhältnis. Die stärkere Beschattung in RH dagegen führte zu einem verminderten Blatt-Trockenmassegehalt sowie teilweise, vor allem bei frisch beschatteten Pflanzen, zur Reduktion der Biomasse- und Blatterträge. Die gemessenen Qualitätsparameter Gesamtphenole, antioxidative Kapazität (ORAC) sowie die Konzentrationen an ätherischem Öl und RA wurden nicht reproduzierbar durch die moderate Lichtreduktion in GG beeinflusst. Auch die stärkere Beschattung in RH hatte keinen gesicherten Einfluss auf die Konzentration an ätherischem Öl. Gesamtphenole, antioxidative Kapazität und RA-Gehalt waren unter der stärkeren Lichtreduktion in RH hingegen reduziert. Unterschiede der Pflanzen-, Ertrags- und Qualitätsparameter zwischen den untersuchten Genotypen zeigten bis auf die Konzentration an ätherischem Öl, die beim Genotyp Lemona am höchsten war, kein reproduzierbares Muster. Die Unterschiede zwischen den Versuchsstandorten waren größer, was auf eine stärkere Bedeutung der Umweltbedingungen im Vergleich zu den Genotypen hinweist. Es lässt sich schlussfolgern, dass die Verwendung von stärker schattierenden Netzen unter den getesteten Anbaubedingungen als negativ zu werten ist, während der Anbau von Zitronenmelisse unter Verwendung von Pflanzenschutznetzen mit moderater Lichtreduktion bei vergleichbaren Standortbedingungen möglich ist.
Keywords: ddc:630